Teori Maslahat Dalam Perceraian : Studi Pasca Berlakunya UU No. 1 Tahun 1974 Dan Kompilasi Hukum Islam - Jamaluddin, Jamaluddin (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2012)
Divorce is something that is not expected to occur in a marriage,  because  the  purpose  of  marriage  is  to  establish a happy  and  eternal  family.  However,  not  all  marriages can be a happy  marriage  and  last  forever.  When  the  conflict  happens between husband and wife and there  is  no  more  peaceful solution, the law gives alterative to a divorce, so the husband and wife  can  get  out  of  the  crisis.  Anyway,  divorce  should  not happen too easily, and according to the hopes of the couple. In the  Law  Number  1  in  1974  concerning  Marriage  and Compilation of Islamic law which one of the purposes is to give welfare,  if  the  divorce  is  chosen  as  alternative  solution  to  the family crisis.